1976
DOI: 10.1084/jem.144.6.1657
|View full text |Cite
|
Sign up to set email alerts
|

Activation of stimulus-specific serine esterases (proteases) in the initiation of platelet secretion. I. Demonstration with organophosphorus inhibitors.

Abstract: The effect of organophosphorus inhibitors of serine esterases (proteases) on secretion from washed rabbit platelets was examined. Five noncytotoxic stimuli were employed: collagen, thrombin, heterologous anti-platelet antibody (in the absence of complement), rabbit C3 bound to zymosan, and platelet activating factor derived from antigen-stimulated, IgE-sensitized rabbit basophils. Diisoprophyl phosphofluoridate, three series of p-nitrophenyl ethyl phosphonates, and a series of cyclohexyl phenylalkylphosphonofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Our findings of poor outcomes in young men was consistent with reports from other cohorts in South Africa and eastern Africa [22][23][24]. In addition, a 2017 report showed that men aged 15-24 years had the lowest proportion of VS (41.5%) [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings of poor outcomes in young men was consistent with reports from other cohorts in South Africa and eastern Africa [22][23][24]. In addition, a 2017 report showed that men aged 15-24 years had the lowest proportion of VS (41.5%) [20].…”
Section: Discussionsupporting
confidence: 91%
“…Given the migratory nature of the male population, being LTFU and changes in service provider are common. Additionally, inconsistent care for this population has had a documented effect of VF and death [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Work is now in progress to define whether the induction of the active component is related to the functions of microtubules or microfilaments. Very recently, ligand-specific esterase activation was observed by Henson et al (29) in the secretion process of platelet. If this situation could be applied to lymphocytes, the specific esterase might be activated by anti-Ig and it might be responsible for the activation of the cytoplasmic factor.…”
Section: Discussionmentioning
confidence: 93%
“…However, anaphylatoxin activity can be detected in vivo in several species (22,23) in spite of fluid-phase regulatory mechanisms. Besides these humoral factors, a regulatory phenomenon on the target cell level has been observed (3,24,25) : after incubation of cells with an anaphylatoxic stimulus, they do not respond a second time to the same or a related stimulus. Desensitization turned out to be stimulus specific.…”
mentioning
confidence: 99%